2023
DOI: 10.1021/acsnano.3c03363
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Electronic Transport and Hysteresis at Individual Grain Boundaries in Hybrid Perovskites via Automated Scanning Probe Microscopy

Abstract: Underlying the rapidly increasing photovoltaic efficiency and stability of metal halide perovskites (MHPs) is the advancement in the understanding of the microstructure of polycrystalline MHP thin film. Over the past decade, intense efforts have been aimed at understanding the effect of microstructures on MHP properties, including chemical heterogeneity, strain disorder, phase impurity, etc. It has been found that grain and grain boundary (GB) are tightly related to lots of microscale and nanoscale behavior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…42 While the systematic study exploring the structure−property relationships associated with the strain-controlled MHP films utilizing spatially resolved electrical and chemical characterization techniques is required, the global impact of K+ distribution in the MHP films is evidenced by the c-AFM analysis. 38,40,43,44 With the micro-strain control, we observed that hybrid B and C samples generate higher conductivity in light and dark conditions compared to samples A and D. These results are in agreement with Figure S5 and Table S1 featuring the calculated PCE from J−V curves. Sample B, which represents the most efficient solar cell in the series, produces photocurrent upward of 300 pA in light on and 120 pA in dark conditions.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…42 While the systematic study exploring the structure−property relationships associated with the strain-controlled MHP films utilizing spatially resolved electrical and chemical characterization techniques is required, the global impact of K+ distribution in the MHP films is evidenced by the c-AFM analysis. 38,40,43,44 With the micro-strain control, we observed that hybrid B and C samples generate higher conductivity in light and dark conditions compared to samples A and D. These results are in agreement with Figure S5 and Table S1 featuring the calculated PCE from J−V curves. Sample B, which represents the most efficient solar cell in the series, produces photocurrent upward of 300 pA in light on and 120 pA in dark conditions.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…Extensive research has been dedicated to improving the efficiency and stability of PSCs by mitigating hysteresis. Previous studies have revealed that GBs in perovskite films play a crucial role in ion migration pathways. , In order to investigate the influence of A-site doping on the GB regions, we utilized KPFM and C-AFM to measure the surface potential and current of the three thin films. The surface potential images of the three thin films under dark and illuminated conditions are depicted in Figure a–f.…”
Section: Results and Discussionmentioning
confidence: 99%
“…With the maturity of machine learning and computer vision technology, it has more and more extensive applications in the field of scanning probe microscope. [16][17][18][19] For example, it is able to divide grain boundaries [20] and classify lattice structures, [21] and it can be applied in cell detection and shape distinction. [22] With the help of the software of computer vision, various methods mainly based on feature matching make it possible to achieve atom tracking.…”
Section: Introductionmentioning
confidence: 99%